The Analysis of Factors Influencing Medication Adherence Behavior Among Pulmonary Tuberculosis Patients - Afifa Rakfi, Nur; Indah Dewi Aurora, Wahyu; Marhami Iskandar, Mirna (Scientific Of Environmental Health and Diseases, 2025)
Background: Pulmonary tuberculosis (TB) remains a major public health problem because poor medication adherence can lead to treatment failure, continued transmission, and drug-resistant TB. Therefore, this study aims to analyze the factors influencing medication adherence behavior among pulmonary tuberculosis patients Methods: This study employed an analytic observational design with a cross-sectional approach involving pulmonary tuberculosis patients undergoing treatment at public health centers in Jambi City, with 105 respondents selected through consecutive sampling. Knowledge, attitudes, and family support were measured using structured questionnaires to assess their association with medication adherence, and data were analyzed using the chi-square test at a significance level of p < 0.05.Results: The findings revealed that more than half of the respondents were not compliant with TB treatment (56.2%). Most participants demonstrated limited knowledge (65.7%) and unfavorable attitudes toward treatment (61%), although a majority reported receiving family support (68.6%). Statistical analysis identified significant associations between medication adherence and knowledge (PR = 4.609; p = 0.000), attitude (PR = 1.722; p = 0.008), and family support (PR = 1.175; p = 0.012). Conclusion: Knowledge, attitude, and family support were significantly related to treatment adherence among pulmonary TB patients in Jambi City in 2024. These results underscore the need for comprehensive TB education initiatives, enhanced communication skills among health workers, and stronger implementation of the DOTS strategy, including digital reminder tools, to improve patient adherence.